The use of a blog and its tools in mathematics teaching and learning (Research, Society and Development, 2019)
Based on experiences in the classroom and the introduction of computers in the educational environment, the intention of this work was the creation and use of a mathematics blog capable of providing resources and assisting in the teaching-learning process by teachers, students and people interested in deepening in the area, taking into account the possible contributions of new technologies for the development and elaboration of concepts and mathematical contents. It was proposed to conduct a qualitative and quantitative research with the objective of collecting data on the application of the methodology, where 251 individuals (students) were randomly assigned to a school in the municipality of Paragominas, highlighting information on the use of computers, a study of mathematics and other important information that helped to develop and improve the contents of the blog. Research, anchored to research, allowed the construction of a knowledge channel capable of supporting the teacher, with contents, materials and suggestions of different classes, allowing a deeper interaction between teacher, parents, students and community, as well as the dissemination of contents in a digital environment.